APPLICATION DETERMINANT HEALTHY FOOD EXPERT TO SUPPORT THE NEEDS OF NURSING MOTHERS - Zahra Zainun Hayatie; Diny Vellyana; Muhamad Muslihudin (IJISCS (International Journal of Information System and Computer Science), 2019)
determination of breastfeeding mothers of healthy foods is one of the processes to Determine the level of quality of the food eaten by the mother during suckling. The Process of Determining healthy food to support the needs of breastfeeding mothers are usually still manual, the breastfeeding mothers should consult midwife or health canters nearby to find healthy food and health level of healthy foods that are consumed during lactation that the nursing mothers are sometimes difficult, for the midwife or health canters diligence takes time for consultation and moms find it difficult, if you have to carry the baby, especially a baby that is still under 5 months. In order to Overcome the problems that happened made design and construction Application Specialists Determinants Healthy Foods Needs to Support Breastfeeding. The method used for application development expert determinants of healthy foods to support the needs of breastfeeding mothers using Data Flow Diagrams (DFD). The end result of the design and construction of this expert application is the existence of a web-based mobile web that can provide easy access to information and the process of defining healthy and unhealthy food nursing mothers to Become more effective and efficient